Deterministic model for the transport of energetic particles: Application in the electron radiotherapy. Issue 8 (December 2015) - Caron, J.; Feugeas, J.-L.; Dubroca, B.; Kantor, G.; Dejean, C.; Birindelli, G.; Pichard, T.; Nicolaï, P.; d'Humières, E.; Frank, M.; Tikhonchuk, V.
Highlights: A deterministic type dose calculation code is proposed in electron radiotherapy. Dose deposition simulation comparisons are led with a Monte Carlo code GEANT4. The comparison of energetic angular particles distributions for both codes is done. Calculation time and computation efficiency is also reported. Abstract: A new deterministic method for calculating the dose distribution in the electron radiotherapy field is presented. The aim of this work was to validate our model by comparing it with the Monte Carlo simulation toolkit, GEANT4. A comparison of the longitudinal and transverse dose deposition profiles and electron distributions in homogeneous water phantoms showed a good accuracy of our model for electron transport, while reducing the calculation time by a factor of 50. Although the Bremsstrahlung effect is not yet implemented in our model, we propose here a method that solves the Boltzmann kinetic equation and provides a viable and efficient alternative to the expensive Monte Carlo modeling.